J.G. Randall and Ruth Painter Randall papers - Randall, J. G. (James Garfield), 1881-1953.; Randall, Ruth Painter; Randall, Ruth Painter
Correspondence, memoranda, diaries, journal, speeches, writings, research materials, printed matter, financial records, and other papers primarily concerning J.G. Randall's works on Abraham Lincoln and on the Civil War. Also includes materials relating to Randall's tenure as professor of history at the University of Illinois at Urbana-Champaign and to Ruth Painter Randall's research and writings, especially her book titled Mary Lincoln; Biography of a Marriage (1953).
Correspondents include Paul M. Angle, William E. Baringer, Roy P. Basler, Howard K. Beale, Henry Steele Commager, Avery Craven, Bernard Augustine De Voto, David Herbert Donald, Frank Burt Freidel, William Best Hesseltine, Reinhard H. Luthin, David C. Mearns, George Fort Milton, Jay Monaghan, Jeanette Paddock Nichols, Roy F. Nichols, Theodore Calvin Pease, David Morris Potter, Harry E. Pratt, Milo Milton Quaife, Carl Sandburg, Wendell Holmes Stephenson, Bell Irvin Wiley, and T. Harry Williams.
J.G. Randall: author, historian, and educator. Ruth Painter Randall: biographer; born, 1892; died, 1971.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Angle, Paul M. -- 1900-1975 -- Correspondence; Baringer, William E. -- 1909-2000 -- Correspondence; Basler, Roy P. -- 1906-1989 -- Correspondence; Beale, Howard K. -- 1899-1959 -- Correspondence; Commager, Henry Steele, -- 1902-1998 -- Correspondence; Craven, Avery, -- 1886-1980 -- Correspondence; De Voto, Bernard Augustine, -- 1897-1955 -- Correspondence; Donald, David Herbert, -- 1920-2009 -- Correspondence; Freidel, Frank, -- 1916-1993 -- Correspondence; Hesseltine, William Best, -- 1902-1963 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Mary Todd, -- 1818-1882.; Luthin, Reinhard H. -- 1905-1962 -- Correspondence; Mearns, David C. -- 1899-1981 -- Correspondence; Milton, George Fort, -- 1894-1955 -- Correspondence; Monaghan, Jay, -- 1891-1980 -- Correspondence; Nichols, Jeannette Paddock, -- 1890-1982 -- Correspondence; Nichols, Roy F. -- 1896-1973 -- Correspondence; Pease, Theodore Calvin, -- 1887-1948 -- Correspondence; Potter, David Morris -- Correspondence; Pratt, Harry E. -- 1901-1956 -- Correspondence; Quaife, Milo Milton, -- 1880-1959 -- Correspondence; Sandburg, Carl, -- 1878-1967 -- Correspondence; Stephenson, Wendell Holmes, -- 1899-1970 -- Correspondence; Wiley, Bell Irvin, -- 1906-1980 -- Correspondence; Williams, T. Harry -- 1909-1979 -- Correspondence; University of Illinois at Urbana-Champaign.; Universities and colleges -- Illinois; United States -- History -- Civil War, 1861-1865.; Authors; Biographers; Educators; Historians